Konstytucyjne podstawy klauzuli wyrzeczenia się wojny a obecna japońska sytuacja polityczna - Depta, Maria (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2016)
The Author of this work takes on the clause renouncing war in the face of the new anti-pacifism policy of Japanese Prime Minister Shinzo Abe. The trial is subjected to study the state system, the Constitution and the specific characteristics of the legal system. The Author tries to prove that the key to the new perception of the clause renouncing war turns out, often appearing in Japan, the difference between the written laws of its application. The study refers to the official statistics, scientific studies, as well as press articles
Keywords: klauzula wyrzeczenia się wojny; Siły Samoobrony; Konstytucja Japonii; Japonia; premier Shinzo Abe; Abe Shinzō (1954-2022 )